Digital Transformation and Sustainability Strategies of Islamic Broadcast Media in Indonesia: A Multiple-Case Study - Ahmad Salman Farid; Eric Msughter Aondover; Irma Yusriani Simamora (Profetik: Jurnal Komunikasi, 2026)
This conceptual study develops a maqasid-based governance framework for Islamic journalism in the post-truth era. The increasing circulation of disinformation, algorithmic bias, and ethical challenges in digital communication environments has raised concerns regarding cognitive security, social cohesion, and national resilience. Using an integrative literature review approach, this study analyzes 20 scholarly sources indexed in Scopus and other relevant academic databases published between 2023 and 2025. The analysis identifies four key governance dimensions of Islamic journalism: cognitive security, ideological cohesion, digital sovereignty, and civic empowerment. Based on these dimensions, the study proposes the Tauhidi Algorithmic Journalism Model, which consists of maslahah-oriented content filtering, real-time tabayyun verification, ethical narrative prioritization, and algorithmic transparency. In addition, the study introduces a preliminary Digital Tauhid Index as a conceptual instrument for assessing the alignment of digital platforms with Islamic communication ethics. The contribution of this study is primarily conceptual, providing a theoretical framework for strengthening Islamic journalism governance in digital media ecosystems. As the proposed model and index have not yet been empirically validated, further expert evaluation and field-based research are required to assess their applicability and effectiveness.